Challenges in Learning English Prepositions by Kuwaiti EFL Learners: A Call for Bridging the Gap in Kuwait’s New English Language Curriculum - Alotaibi, Abdullah M.; Wu, Shu-hua; Alrabah, Sulaiman (Advances in Social Sciences Research Journal, 2018)
This paper investigates the extent to which 80 students of bachelor and diploma’s degree studying in PAAET are aware of the appropriate use of simple and complex prepositions in English. It is one paper within a series of papers that shed light on the areas of difficulties and challenges currently facing EFL learners in Kuwait who have graduated from government schools and have studied the English language curriculum implemented until 2016. In addition, it represents a base line to which the competence of Kuwaiti EFL learners can be measured and compared to the outcomes of the new curriculum which was implemented in 2016 (graduates of the new curriculum should be joining PAAET three years from now). In this paper, two groups of participants divided based on proficiency levels were given a multiple-choice test which was used to check their comprehension skills in choosing the right preposition in English. Error analysis revealed that 53.75% of students have difficulty in learning English prepositions and these difficulties co-relate to low levels of English proficiency. The research shows that Kuwaiti EFL learners have little awareness of English prepositions due to a number of reasons including L1 negative transfer and the intralingual errors. The researchers hope that the implementation of the new English curriculum should encompass linguistics, cognitive and effective goals in teaching and learning English prepositions if it takes into consideration the common errors Kuwaiti EFL learners perform.